Penerapan Terapi Cobra untuk Merubah Karakter Siswa SMAN 7 Mataram - Tri Sari Wijayanti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2018)
Abstract: Character is inherent and formed in someone. To change the characters, it requires a process. Thehigh school level education psychologically can be claimed as education in changes that is quite heavy. Thelimited number of teachers compared to the number of students, social interaction and situational time hadbeen very possible to be the cause. The implementation of Cobra Therapy (Joint Example of BehaviourRegulation) applied had been in accordance with CBT Methods i.e. an approach to the root of cognitivetherapy (persuasion, challenging, debate, hypothesizing, cognitive restructuring, and internal debate). Theresults of the study obtained that the COBRA therapy program compiled and implemented was as a form ofcoaching efforts that were more intensive and specific to students who had the problems. The implementation of COBRA therapy at SMAN 7 Mataram was very effective as an alternative problem solving for students in improving the character education. Abstrak: Karakter memang sudah melekat dan terbentuk pada diri sesorang. Untuk merubahnya memerlukan proses. Pendidikan pada jenjang SMA, secara psikologis dapat dikatakan sebagai pendidikan pada perubahan yang cukup berat. Terbatasnya jumlah guru dibandingkan dengan jumlah siswa, waktu interaksi dan situasional sosial sangat dimungkinkan sebagai penyebabnya. Pelaksanaan Terapi Cobra (Contoh Bersama Regulasi Ahklak) yang diterapkan sesuai dengan CBT Methods yaitu teknik pendekatan dengan akar terapi kognitif (persuasion, challenging, debate, hypothesizing, cognitive restructuring, and internal debate). Hasil yang didapatkan bahwa program terapi COBRA yang disusun dan dilaksanakan sebagai bentuk upaya pembinaan yang lebih intensif dan spesifik terhadap siswa-siswa yang bermasalah. Pelaksanaan terapi COBRA di SMA Negeri 7 Mataram sangat efektif sebagai alternatif pemecahan masalah siswa dalam meningkatkan pendidikan karakter